Off-axis optical quadruple racetrack resonator: performance optimization. (2nd January 2019) - Addya, Subhankar; Dey, Sabitabrata; Mandal, Sanjoy
Abstract: Optical asymmetric off-axis quadruple racetrack resonator based on optical signal processing technique has been analyzed in this work for detecting its filter performance in terms of optimization of the crosstalk and resonance loss. The analytical approach utilized for deriving the transfer function of the filter is based on Mason's gain formula and Vernier principle. The constituent material employed for developing this architecture is Silicon-on-Insulator (SOI). Light wave from the optical source at the in port enters the designed system and comes out through the drop port of two racetrack resonators that are in close proximity with output waveguide. Crosstalk level and resonance losses get minimal while calculating drop port transmittance at resonance. It is shown in this work that coupling coefficients largely contribute in crosstalk and resonance loss optimization. The extended FSR achieved in this architecture also proves its candidature in diverse fields of photonics, i.e. optical lasing and THz communication. The optimum resonance loss and crosstalk level, crosstalk suppression bandwidth are also investigated in this paper.